Effects of Transcranial Direct Current Stimulation on Upper Limb Muscle Strength and Endurance in Healthy Individuals: A Systematic Review and Meta-Analysis - Hu, Kun; Chen, Yu; Guo, Feng; Wang, Xin (Frontiers in Physiology, 2022)
Objective Whether transcranial direct current stimulation (tDCS) can improve upper limb muscle strength and endurance in healthy subjects is still controversial. This article reviews the relevant literature on the use of tDCS to improve upper limb muscle strength and endurance in healthy individuals. Methods We systematically searched the Cochrane Library, PubMed, EMBASE, and the Web of Science until September 4, 2021. Randomized parallel or crossover experimental studies on the effects of tDCS on upper limb muscle strength and endurance in healthy individuals were included. Review Manager 5.3 software was used to evaluate methodological quality and analyze the combined effect of the included literature. Results Twelve studies (189 participants) were included in the qualitative synthesis, and nine studies (146 participants) were included in the meta-analysis. Compared with the control group, the tDCS intervention had no significant effect on improving upper limb muscle strength [I2 = 0%, 95% CI (−0.79, 0.23), p = 0.98, MD = 0.01]. In this analysis, tDCS had a significant heterogeneity (I2 = 87%) in improving upper limb muscle endurance compared with the control group. After the subgroup analysis and the sensitivity analysis, the source of heterogeneity was excluded. The final results showed that tDCS had a significant effect on improving upper limb muscle endurance [I2 = 0%, 95% CI (1.91, 4.83), p < 0.00001, MD = 3.37]. Conclusions tDCS has no significant effect on improvement of upper limb muscle strength, but has a significant effect on improving upper limb endurance performance (especially on the non-dominant side).